Motorcycle Dolly Mover version 2 (MDM2) / Suhaimi Nayan ... [et al.] - Nayan, Suhaimi; Nayan, Surina; Abdul Rahman, Amir Shauqee; Mohamad Fazli, Nurul Izzati; Ahmad Fuad, Abdul Qayyum; Mohd Tamizi, Muhammad Firhan (Universiti Teknologi MARA, Negeri Sembilan, 2023)
The Motorcycle Dolly Mover project (MDM2) is an improvement project from an existing product which is available in the market. “Dolly” means a small platform on wheels which is used to carry heavy objects. Motorcycle dolly is one of the most often used support equipment to move motorcycles. This project (MDM 2) is devoted to every motorcycle enthusiast who wants to work around his/her bike, especially in confined spaces. Thus, a decent dolly is needed to help him/her to easily move his/her motorcycle. The main objective of the project is to improve the current project and overcome its weaknesses. The current available dolly mover in the market is bulky and heavy. Thus, making it difficult for the user to carry it anywhere he/she goes especially women. In addition, its design and size are not suitable for people with weak hand muscles, as it requires a lot of energy to lift the motorcycle onto the dolly. In addition, the current dolly is not equipped with a security system in case of theft. As a result, MDM2 is introduced to improve the current available dolly in the market. The new dolly, MDM2 is more user friendly and comfortable as it is light and not bulky. As a result, it is suitable for people with weak hand muscles and women. For theft prevention, it has a security function that can alert the owner when someone tries to move the motorcycle. Finally, it is also capable of withstanding any motorcycle loads of up to 400kg.